Development and Evaluation of Enzyme-Linked Viral Immune Capture Assay for Detection of SARS-CoV-2 - Alharbi, Naif Khalaf; Samman, Nosaibah; Alhayli, Sadeem; Alghoribi, Majed F.; Almasoud, Abdulrahman; Nehdi, Atef (Frontiers in Bioengineering and Biotechnology, 2022)
The pandemic of COVID-19 was caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) in 2019, and that has prompted unprecedented research activities for vaccines, therapeutics, and diagnostics. The real-time reverse transcriptase polymerase chain reaction (RT-PCR) is the gold standard method of diagnosis; however, immune-based assays offer cost-effective, deployable, easy-to-read solutions for diagnosis and surveillance. Here, we present the development, optimization, and testing of an Enzyme Linked Viral Immune Capture Assay (ELVICA). It utilizes the spike antigen as the detected target of the virus and antibody-coated beads to capture the virus and enrich the detection. This method can be read-out by luminescent and colorimetric equipment. It can also be visualised by imaging system, offering a variety of detection approaches. ELVICA showed specificity to SARS-CoV-2 pseudotyped viruses as compared to MERS-CoV pseudotyped viruses. As compared to RT-PCR, ELVICA showed a high compatibility in detecting the virus in patient respiratory samples, especially for samples that are below a Ct value of 32 in RT-PCR. This assay is readily adaptable for detecting other pathogens, which serve as a quick and affordable diagnostic tool.